2016
DOI: 10.1093/deafed/enw057
|View full text |Cite
|
Sign up to set email alerts
|

Social Maturity and Executive Function Among Deaf Learners

Abstract: Two experiments examined relations among social maturity, executive function, language, and cochlear implant (CI) use among deaf high school and college students. Experiment 1 revealed no differences between deaf CI users, deaf nonusers, and hearing college students in measures of social maturity. However, deaf students (both CI users and nonusers) reported significantly greater executive function (EF) difficulties in several domains, and EF was related to social maturity. Experiment 2 found that deaf CI users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
1
14
0
2
Order By: Relevance
“…Associations between psychosocial functioning and EF have been previously reported in studies of children, adolescents, and young adults with CIs. For example, Barker et al (2009) and Marschark et al (2017) found that EF delays may underlie specific areas of maladaptive psychosocial functioning. Parents of pediatric CI candidates report that their deaf children (under 5 years of age and on track for cochlear implantation) display aggressive behaviors within age-appropriate limits (Barker et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Associations between psychosocial functioning and EF have been previously reported in studies of children, adolescents, and young adults with CIs. For example, Barker et al (2009) and Marschark et al (2017) found that EF delays may underlie specific areas of maladaptive psychosocial functioning. Parents of pediatric CI candidates report that their deaf children (under 5 years of age and on track for cochlear implantation) display aggressive behaviors within age-appropriate limits (Barker et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Barker et al (2009) also found that behavioral measures of sustained attention (a core executive function) significantly predicted parent-reported internalizing behaviors. Marschark et al (2017) reports that deaf adolescents and young adults (with and without CIs) do not significantly differ from their NH peers with respect to social maturity. However, these deaf individuals did differ on several domains of EF, and delays in attention and visual–spatial organization specifically were related to social immaturity in CI users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original LEAF was a parent-report measure. The present study used a language-revised, self-report version of the instrument designed and validated for use with deaf and hearing college students by Marschark, Kronenberger, et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…( ‫ثٚ‬ ‫ٝأُؾ٤ط٤ٖ‬ ‫أهواٗٚ‬ ‫ٓغ‬ ‫ا٫عزٔبػ٢‬ ‫اُزلبػَ‬ ‫ك٢‬ ‫ٝٙؼق‬ ‫اًَُِٞ٤خ‬ ‫أٌُْ٬د‬ ٖٓ ‫اٌُض٤و‬ Botting et al, 2017;Hintermair, 2013;Marschark et al, 2017 . ) ‫ا٫ٗلؼبُ٢‬ ‫اُز٘ظ٤ْ‬ ‫ٝ٣ؼزجو‬ Emotional regulation ‫ا٫ٗلؼبُ٢‬ ‫اُ٘ٔٞ‬ ‫ٗظبّ‬ ‫كافَ‬ ‫ر٘ٔٞ‬ ‫ٓؼولح‬ ‫ػِٔ٤خ‬ ‫اُز٢‬ ‫ا٫ٗلؼب٫د‬ ‫ػِ٠‬ ‫ثبُزؼوف‬ ‫ُِلوك‬ ‫٣َٔؼ‬ ‫ؽ٤ش‬ ‫اُِلظ٢،‬ ‫ؿ٤و‬ ‫اُزٞإَ‬ ‫ك٢‬ ‫أٍبٍ٢‬ ‫ػٖ٘و‬ ٞٛٝ ‫ُِلوك،‬ ‫اُْبَٓ‬ ‫ٝرل‬ ‫ا٥فو٣ٖ‬ ‫اٗلؼب٫د‬ ‫كْٜ‬ ‫رزٖٚٔ‬ ‫ًٔب‬ ‫ٓؼٜب،‬ ‫ٝاُزؼبَٓ‬ ‫ػٜ٘ب‬ ‫اُزؼج٤و‬ ‫٣زْ‬ ‫ثٜب،‬ ‫ٝاُز٘جإ‬ ‫ٝرٖوكبرْٜ‬ ‫أػٔبُْٜ‬ ‫َ٤و‬ ‫ػِ٠‬ ‫مُي‬ ‫٣٘طٞ١‬ ‫ٝهل‬ ‫رغبْٜٛ.‬ ‫ٝاُلؼبُخ‬ ‫أُ٘بٍجخ‬ ‫ا٧كؼبٍ‬ ‫ثوكٝك‬ ‫ٝاُو٤بّ‬ ‫ُِلوك،‬ ‫ا٫ٗلؼبُ٤خ‬ ‫اُؾبُخ‬ ‫ػِ٠‬ ‫ٝاَُ٤طوح‬ ‫اُقٞف‬ ‫أٝ‬ ‫اُؾيٕ‬ ‫ػ٬ٓبد‬ ‫ئفلبء‬ ‫أٝ‬ ‫اُوِن،‬ ‫أٝ‬ ‫اُـٚت‬ ‫ُزوِ٤َ‬ ‫ٕؼت‬ ‫ٓٞهق‬ ‫ك٢‬ ‫اُزلٌ٤و‬ ‫ئػبكح‬ ‫ٓضَ‬ ‫ًٍِٞ٤بد‬ ‫أ‬ ‫ػِ٠‬ ‫اُزوً٤ي‬ ‫أٝ‬ ‫أُوئ٤خ،‬ ‫اُٜلٝء‬ ‫أٝ‬ ‫ثبَُؼبكح‬ ‫اُْؼٞه‬ ‫ٍجبة‬ (Soltanifar et al, 2018) ‫اُز٘ظ٤ْ‬ ‫٣ؼل‬ ‫ًٔب‬ .…”
mentioning
confidence: 99%